Applications of rare earth elements in cancer: Evidence mapping and scientometric analysis - Wang, Jinyu; Li, Sheng (Frontiers in Medicine, 2022)
Cancer is one of the most important public health issues worldwide. Radiation therapy (XRT), chemotherapy, and targeted therapy are some of the main types of cancer therapy. Metals are used extensively in cancer diagnosis and therapy, and rare earth elements occupy an important niche in these areas. In recent years, an increasing number of studies have focused on the application of lanthanides in cancer diagnosis and therapy. However, no research has analyzed the current status and future trends of lanthanides in treating cancer. We downloaded data from publications from the Web of Science Core Collection. We used VOSviewer software to analyze literature information, including publication years, journals, countries, institutes, authors, keywords, and co-cited references. A total of 7849 publications were identified. The first study on the association of rare earth elements with cancer was published in 1945. After 1980, the number of yearly publications has increased. The USA was the most productive country, and the institution with the most frequent contributions was the Chinese Academy of Sciences . We observed close collaboration between countries and between institutes. The 7839 publications were published in 1579 journals, and Radiology was both the most productive journal and cited journal. The main research topics in the application of lanthanide complex-doped nanomaterials in the diagnosis and treatment for cancer include magnetic resonance imaging contrast agents, photodynamic therapy, anticancer drug delivery, the efficacy and safety of yttrium-90 radioimmunotherapy and chemoembolization for the treatment of HCC, gadolinium magnetic resonance imaging (MRI) contrast agent for cancer diagnosis, and cerium oxide nanoparticles. In recent years, especially since 2016, the research frontiers are emerging in cerium oxide nanoparticles and photodynamic therapy. Studies related to the application of rare earth elements and cancer have significantly increased over the past 20 years. The United States contributed the most articles in the field, followed by China and Germany, and cooperation among countries was frequent. The Chinese Academy of Sciences, Northwestern University, and Stanford University were the three most productive institutions, and cooperation among institutions was frequent. Many high-quality journals have published relevant research, but there are few highly productive journals.